Effect of human colostrum and infant formula on the phagocytic activity of macrophages. I. Resident and stimulated mouse peritoneal macrophages. - Hughes, A (1985)
Phagocytosis and degradation of radiolabelled human transferrin-anti-transferrin immune complexes by resident and stimulated mouse peritoneal macrophages was inhibited by liquid infant formula, particularly in the case of resident cells. Mouse peritoneal macrophages exposed to infant formula were shown by immunofluorescence to bind casein and beta-lactoglobulin, but there was little binding of alpha-lactalbumin. Comparison of various artificial milks, cow's milk and purified casein indicated that both the concentration and the degree of denaturation of casein may be important in the impairment of macrophage function by milk. It is suggested that bottle feeding of infants might result in impairment of macrophage function in the small intestine.